1994
DOI: 10.1128/aem.60.2.408-415.1994
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Ecological Characteristics of a Nodule-Dominant Serotype from an Indigenous Soil Population of Rhizobium leguminosarum bv. trifolii

Abstract: Although at least 13 antigenically distinct serotypes of Rhizobium leguminosarum bv. trifolii exist in an Abiqua silty clay loam soil, one serotype, AS6, occupies .50% of the root nodules formed on field-grown subclover and between 33 and 78% of the nodules formed on five annual clover species grown in the same soil under laboratory conditions. The dominance of subclover nodules by serotype AS6 was reproducible over a 4-year sampling period and throughout the entire 200by 100-m pasture examined. Serotype AS6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 54 publications
(59 reference statements)
1
16
1
Order By: Relevance
“…Because soil bacteria are generally resilient to stress (Paul & Clark 19891, and because most of the soil volume is a nutrient poor, highly porous and discontinuous matrix, soil may favour the persistence of a large number of genotypic variants of a species and foster the develop ment of nonclonal population structure (Bottomley 1993). Alternatively, soil contains nutrient-rich microenvironments such as the root-soil interface where sufficient energy exists to allow superior genotypes to undergo clonal expansion by binary fission (Leung et al 1994a). Since enhanced microbial growth in soil microenvironments is invariably accompanied by an enhanced rate of predation by protozoans and nematodes (Christensen et nl.…”
Section: Introductionmentioning
confidence: 99%
“…Because soil bacteria are generally resilient to stress (Paul & Clark 19891, and because most of the soil volume is a nutrient poor, highly porous and discontinuous matrix, soil may favour the persistence of a large number of genotypic variants of a species and foster the develop ment of nonclonal population structure (Bottomley 1993). Alternatively, soil contains nutrient-rich microenvironments such as the root-soil interface where sufficient energy exists to allow superior genotypes to undergo clonal expansion by binary fission (Leung et al 1994a). Since enhanced microbial growth in soil microenvironments is invariably accompanied by an enhanced rate of predation by protozoans and nematodes (Christensen et nl.…”
Section: Introductionmentioning
confidence: 99%
“…In symbiotic rhizobacteria like Rhizobium species, the evolution of the population structure may be influenced by environmental conditions like biological barriers to gene exchange or geographical isolation and also by the type of soil or the genotype of the host plant (8). It is known that legumes can be preferentially nodulated by one of two rhizobial strains even if the preferred strain is outnumbered by the other strain (28,44). However, little is known about the relationships between the genetic polymorphism within a Rhizobium population and the preferences for nodulating particular genotypes of compatible host plants (28).…”
mentioning
confidence: 99%
“…It is known that legumes can be preferentially nodulated by one of two rhizobial strains even if the preferred strain is outnumbered by the other strain (28,44). However, little is known about the relationships between the genetic polymorphism within a Rhizobium population and the preferences for nodulating particular genotypes of compatible host plants (28). One additional element that can also play a critical role in the evolution of Rhizobium populations is the occurrence of large plasmids that can have an evolutionary history different from the evolutionary history of the strains that they live in (39,47).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rhizosphere effect, i.e. the ratio between rhizosphere and non rhizosphere population densities increased much more among the rare serotypes than in the dominant one in spring, while this effect was similar in other seasons (Leung et al, 1994b). Moreover, in a study carried out by Laguerre et al (2003) in France, a difference between fave bean and pea was observed for the relationship of dominance in soil or nodules in the R. leguminosarum bv viceae population.…”
Section: Ecological Aspects Of the Plant-rhizobia Interactionmentioning
confidence: 90%